Demonstration of Playful Interaction Patterns for Head-mounted Device-based AR Experiences in Cultural Heritage ... - Liu, Yu (The Eurographics Association, 2024)
This proposal explores AR applications with engaging interaction patterns to provide immersive and entertaining museum experiences. Focusing on cultural heritage, this demonstration showcases innovative interaction patterns for navigation and exhibit activation. The navigation interaction pattern uses dynamic visual and auditory cues, while the exhibit activation interaction pattern incorporates playful orca-inspired elements. Implemented in Unity3D and deployed on HoloLens 2, the demonstration effectively balances usability and entertainment, enhancing visitor engagement and showcasing new AR possibilities for museums. ... : Poster ...